Development of a Web-Based Based Reproductive Health Learning Platform to Prevent Sexual Violence Among Junior High School Students in Makassar, Indonesia - Andi Asmawati; Asham Bin Jamaluddin; Andi Citra Pratiwi; Muhammad Isrul; Andi Nur Veryani; Fadhilah Azzahra (Biology Teaching and Learning, 2026)
Abstract Purpose: This study aimed to develop and evaluate a web-based learning platform on reproductive health as an educational strategy to prevent sexual violence among junior high school students in Makassar, Indonesia.Research Methodology: This Research and Development (R&D) study employed the ADDIE model and involved students from SMPN 21 Makassar and MTsN 1 Makassar. Data were collected through expert validation sheets, student response questionnaires, and knowledge tests, and were analyzed descriptively using validation scores, percentage analysis, and N-Gain.Results: Expert validation results indicated that both the media and the content were valid, with scores of 4.775 and 4.792, respectively. Practicality testing based on student responses showed a score of 76.30 (interesting category) at SMPN 21 Makassar and 86.78 (very interesting category) at MTsN 1 Makassar. The effectiveness of the platform was analyzed using the N-Gain score derived from pre-test and post-test comparisons. The results showed that SMPN 21 Makassar achieved an N-Gain score of 0.41 (moderate category), while MTsN 1 Makassar achieved an N-Gain score of 0.91 (high category).Conclusions: These findings indicate that the developed web-based learning platform is valid, practical, and demonstrates preliminary effectiveness in improving students’ knowledge of reproductive health and sexual violence prevention.Limitations: This study was conducted as a limited pilot test without a control group and relied on short-term knowledge measurement.Contributions: This platform can be used as a supporting educational tool to enhance students’ understanding of reproductive health, self-protection, and awareness of sexual violence risks.Keywords: Digital media 1, Teenagers 2, Reproductive Health 3.